2016
DOI: 10.1177/1474704916653964
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Perspective on Pain Communication

Abstract: Pain serves as a signal to elicit care from others. In turn, displaying pain might be attractive because of the benefits it might bring. Additionally, displaying pain is easy, because helpers distinguish poorly between genuine pain and faked pain. Hence, helpers face the problem of distinguishing true sufferers from free riders, while sufferers face the problem of communicating need convincingly. This article will propose solutions to these adaptive problems. Based on theoretical arguments and on empirical ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 82 publications
1
21
0
Order By: Relevance
“…Certainly, being vulnerable may provide secondary social gains (see, for example, Gray & Wegner, 2011); at a basic level, credible signals of physical pain show others we need assistance and can generate empathy (K. D. Craig, 2009;K. D. Craig, Versloot, Goubert, Vervoort, & Crombez, 2010;Hadjistavropoulos et al, 2011;Steinkopf, 2016). Shared pain can bring people together (Bastian, Jetten, & Ferris, 2014), but nuanced sociorelational outcomes appear not to be the direct priority of resource accumulation activities after physical pain.…”
Section: Response: Resource Accumulationmentioning
confidence: 99%
“…Certainly, being vulnerable may provide secondary social gains (see, for example, Gray & Wegner, 2011); at a basic level, credible signals of physical pain show others we need assistance and can generate empathy (K. D. Craig, 2009;K. D. Craig, Versloot, Goubert, Vervoort, & Crombez, 2010;Hadjistavropoulos et al, 2011;Steinkopf, 2016). Shared pain can bring people together (Bastian, Jetten, & Ferris, 2014), but nuanced sociorelational outcomes appear not to be the direct priority of resource accumulation activities after physical pain.…”
Section: Response: Resource Accumulationmentioning
confidence: 99%
“…This has a number of implications for the evolution of health and healing: The prosocial environment of humans should favor symptoms that signal suffering convincingly and motivate others to acknowledge the sick state and grant help and treatment (Steinkopf 2015;Tiokhin 2016). Marked displays of pain in humans might be selected for their effectiveness in mobilizing others' support (Finlay & Syal 2014;Steinkopf 2016;Williams 2002). Self-injury and suicidal behavior (Hagen et al 2008;Nock 2008) and the use of invasive and harmful treatments (de Barra & Cownden 2016) have been hypothesized to serve as highly costly signals to convince others of the victim's neediness.…”
Section: Shamanism and The Psychosis Continuummentioning
confidence: 99%
“…The ability of empathy is closely related to the evaluation of other’s pain ( Goubert et al, 2005 ; Decety and Svetlova, 2012 ), but also gives rise to the problem of faking pain to one’s own advantage. Fortunately, previous research has suggested us that both pain ( Steinkopf, 2016 ) and empathy ( Melloni et al, 2014 ) are context-dependent, meaning that people could avoid showing empathy for other’s fake pain with the help of contextual cue. Evolutionally, we would expect children could take advantage of contextual cue (especially physical cue) to show empathy for pain.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have showed that empathy for pain is highly context-dependent ( Gonzalez-Liencres et al, 2013 ; Melloni et al, 2014 ). Thus, people would take advantage of contextual cues to make decisions, as they could provide us explainable information and would benefit causal reasoning ( Steinkopf, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation